Data security, control and privacy management of facebook usage among undergraduate students / Mohamad Ridhuan Mat Dangi ... [et al.] - Mat Dangi, Mohamad Ridhuan (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
Facebook is one of the most popular social networking sites with millions of users around the globe. However, most users overlooked their privacy management where their personal information are exposed and might be misused by others. This study was conducted on 290 respondents on a particular university regarding their Facebook usage upon data security and privacy control. A non-experimental research, particularly descriptive research and correlational research were applied in order to identify whether privacy and data security concerns, perceived privacy control and privacy concerns have a relationship with individual privacy management. Majority (91%) respondents have been using Facebook for more than 2 years, but most of them were not addicted to it. Maintaining relationship with friends and family members were the main reason why the respondents use Facebook. Other reasons given are to join a specific class group or club, to read news, to get the latest information and current issues. The regression analysis shows all hypotheses were supported in which every unit increase in independent variables will increase the dependent variable, while correlation indicated a positive relationship between privacy and data security concerns (PDSC) on Facebook r = .385, and perceived privacy control (PPC) r = .487, with individual privacy management. Privacy concern (PC) showed a moderate positive relationship as represented r = .577.